Evaluating Public Service Performance in Food Safety Certification: The Role of Human Resource Competence, Information Technology, and Process Transparency at BBPOM Bandar Lampung, Indonesia - Mega, Sri Wulan; Sugiono, Arif; Wijaya, Andi (Manunggal Halim Jaya, 2025)
This study aims to evaluate the simultaneous influence of human resource competence, the utilization of information technology, and process transparency on public service performance, particularly in the certification of Good Processed Food Production Methods (CPPOB) at the Food and Drug Supervisory Agency (BBPOM) in Bandar Lampung, Indonesia. Responding to increasing public demands for food safety and the complexity of certification services, this research investigates how administrative and technological factors shape institutional performance. A quantitative approach was employed, involving 275 respondents who had accessed CPPOB certification services. Multiple linear regression analysis was conducted to measure the effect of each independent variable. The findings reveal that all three variables significantly influence public service performance, with human resource competence contributing the most (β = 0.313), followed by information technology (β = 0.152) and process transparency (β = 0.147). The study provides both theoretical and practical implications. Theoretically, it reinforces the discourse of public service delivery based on good governance and public value management. The results highlight the importance of institutional strategies focusing on employee training, digital infrastructure development, and transparent service procedures. These findings contribute to public sector reform efforts in Indonesia, particularly in enhancing responsiveness, efficiency, and accountability in food safety supervision.